Copper Mediates Anti-Inflammatory and Antifibrotic Activity of Gleevec in Hepatocellular Carcinoma-Induced Male Rats - Iftekhar Hassan; Hossam Ebaid; Ibrahim M. Alhazza; Jameel Al-Tamimi; Shazia Aman; Ahmad M. Abdel-Mageed (Canadian Journal of Gastroenterology and Hepatology)
The elevated level of copper is one of the hallmark features of cancer cells in most of the types of cancer. In the present study, this feature has been targeted to investigate if coadministration of exogenous copper (Cu+) and its chelating agent like disulfiram (DSF+) influence the antineoplastic activity of the anticancer drug, Gleevec (GLV+), in hepatocellular carcinoma (HCC)-induced rats via immunomodulation. After the treatment, the level of proinflammatory interleukins (IL-1, 2, 6, and 7), anti-inflammatory interleukin (IL-10) concomitant with transcription factors (NF-kB and TNF-a), and the apoptotic marker (cleaved PARP) was estimated. The cancer-induced group without treatment (CN+) demonstrated abnormally elevated level of all proinflammatory cytokines and transcription factors concomitant with a compromised level of cleaved PARP as compared to the control normal (CN-). The detailed histological analysis also supported the results exhibiting extensive inflammation and tissue fibrosis confirming the second stage of HCC. Cu+, DSF+, and GLV+ displayed mild improvement in most of the parameters, but the combination group GLV + Cu+ demonstrated remarkable recovery in histology and most of the parameters tended towards the CN- followed by GLV + DSF+. Therefore, the management of copper level is critical in realizing the antineoplastic activity of GLV up to its full potential in cancer treatment. These findings will help in improving chemoimmunotherapy and personalized cancer treatment.